Viruses of cucumber isolated from some regions of Ukraine - A. Ryzhkova; T.P. Shevchenko; I.G. Budzanivska; V.P. Polischuk (Plant Protection Science, 2002)
Properties of viruses isolated from cucumbers in greenhouses of Ukraine are characterized in this article by electrophoresis, ELISA, electron microscopy, and immunoblotting.